Produção animal e de grãos de trigo duplo propósito com diferentes períodos de pastejo - Pitta, Christiano Santos Rocha (2009)
The double purpose wheat production (animal and grain production) allows some flexibility in the crop livestock production system and permit to the farmers to choose the best alternative according to the prices paid to the products, although, the deferment periods and the grazing effects over the wheat production need to be studied. The aim of the present work, carried out at the Agronomist institute of Paraná (IAPAR), experimental unit of Pato Branco-PR, was to evaluate the effect of six grazing periods (0, 21, 42, 63, 84 and 105 days) over the wheat grain production, BRS Tarumã cultivar and the animal production of Purunã steers with average live weight of 162 kg and age of 10 months managed on continuous stocking rate. During the experimental period (April to November of 2007) were evaluated: forage mass, offer and nutritive value, intake, stocking rate, animal daily gain and gain per hectare and wheat grain production. The experiment was laid out as randomized complete (RCBD) block design with six treatments and two eplications. The grazing period can be kept until 88 days with efficient results to the animal production, however, the grains production decreased with grazing use.